PEMODELAN PERPINDAHAN MASSA ADSORPSI ZAT WARNA PADA FLORISIL DAN SILICA GEL DENGAN HOMOGENEOUS AND HETEROGENEOUS SURFACE DIFFUSION MODEL - Aditya Putranto; Stephanie Angelina (Research Report - Engineering Science, 2014)
Adsorption process has been extensively applied in many industries for impurities removal and waste water treatment. Activated carbon is one of the most effective adsorbent which is used in adsorption process. Activated carbon has complex structure, that’s why mass transfer characteristics of adsorption process using activated carbon have to be investigated by using model. Mass transfer is influenced by types of adsorbate, initial concentration of dye solution, and temperature.The objectives of this research are to studymass transfer phenomena occurred in dyes adsorption using activated carbon, to determine values of Heterogenous SurfaceDiffusion Model parameters, such as external liquid film mass transfer coefficient (kf), surface diffusion coefficient (Ds), branched pore rate coefficient (kb), and fraction oftotal adsorptive capacity in macropores (f), and to study the effects of adsorbate types, initial concentration of dye solution, and temperature to the values of kf, Ds, kb, and f.This research was carried out by using 2 types of adsorbate, 3 variation of initial concentration, and 4 variation of temperature. Adsorption experiment was carried out inshaking waterbath that had been setted in certain operating condition. Concentration of dye solutions in certain time interval was determined by measuring absorbance usingUV spectrophotometer. Analysis procedures of experimental data in this research consist of several steps: arranging model based on adsorption phenomena, finishingmodel that consists of differential equations, validation between experimental data and model, and determining values of Heterogenous Surface Diffusion Model parameters.The results of this research show that the values of kf, Ds, kb are influenced by types of adsorbate, initial concentration of dye solution, and temperature; if initial concentration increases, the values of kf, Ds, kb will increase; if temperature increases, the values of kf, Ds, kb will increase; the values of kf, Ds, kb for methylene blue solution are greater than methyl orange; the value of f is not influenced by types of adsorbate, initial concentration of dye solution, and temperature; and Heterogenous Surface Diffusion Model is suitable to show mass transfer characteristics that occurs in dyes adsorption using activated carbon.